2021
DOI: 10.1590/1518-8345.5181.3494
|View full text |Cite|
|
Sign up to set email alerts
|

Use of the prone position in pregnant women with COVID-19 or other health conditions

Abstract: Objective: to analyze, in the scientific literature, the knowledge available on the use of the prone position in pregnant women diagnosed with COVID-19 or other health conditions. Method: an integrative literature review developed through the following guiding question: What is the scientific knowledge available on the use of the prone position in pregnant women with COVID-19 or other health conditions? The search for studies was carried out in eight databases. Results: using the prone position in pregnant w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 33 publications
0
11
0
3
Order By: Relevance
“…In ARDS using mechanical ventilation with a high PEEP, low tidal volume and allowing low plateau pressure with permissive hypercapnia, paralytics use for synchrony with the ventilator along with proning remain the cornerstones of therapy. Prone ventilation has been used during pregnancy and reported in the case report series [ 11 ]. Proning provides an augmented ventilation-perfusion ratio while decreasing the compression of the posterior and medial lung, causing a decrease in hypoxic vasoconstriction, an improvement in cardiac output, and recruitment of more alveolar units.…”
Section: Discussionmentioning
confidence: 99%
“…In ARDS using mechanical ventilation with a high PEEP, low tidal volume and allowing low plateau pressure with permissive hypercapnia, paralytics use for synchrony with the ventilator along with proning remain the cornerstones of therapy. Prone ventilation has been used during pregnancy and reported in the case report series [ 11 ]. Proning provides an augmented ventilation-perfusion ratio while decreasing the compression of the posterior and medial lung, causing a decrease in hypoxic vasoconstriction, an improvement in cardiac output, and recruitment of more alveolar units.…”
Section: Discussionmentioning
confidence: 99%
“…[80] This approach may be advantageous in the gravid patient as the modified prone positioning of the patient for this technique alleviates compression of the uterus on the vena cava and is associated with improvements in oxygenation and systolic blood pressure. [66,70,71,81] However, this benefit must be balanced with the higher insufflation pressures that are required for adequate exposure (20-28mmHg), which effectively compresses the IVC. These insufflation pressures have been shown to be safe without significant hemodynamic effects in the general population undergoing right-sided PRA.…”
Section: Timingmentioning
confidence: 99%
“…Recent use of prone positioning in pregnant patients with COVID-19 pneumonia and acute respiratory distress has demonstrated that this positioning is safe, though continuous fetal monitoring is advised. [66,70,71].…”
Section: Timingmentioning
confidence: 99%
“…However, in pregnant patients with moderate to severe ARDS prone positioning has been reported to be safe and effective. [83][84][85][86][87] In addition, the ELSO-based registry reported 58% of pregnant and peripartum patients were prone positioned before ECMO initiation. 81 Modification of prone positioning, especially in patients in the third trimester (24 to 28 wk), involves use of padding or blankets and pillows above and below the gravid uterus to avoid aortocaval compression.…”
Section: Additional Therapiesmentioning
confidence: 99%
“…In nonpregnant patients with ARDS, prone positioning is an effective salvage therapy82 and before the 2019 COVID pandemic, prone positioning was infrequently used in pregnant patients. However, in pregnant patients with moderate to severe ARDS prone positioning has been reported to be safe and effective 83–87. In addition, the ELSO-based registry reported 58% of pregnant and peripartum patients were prone positioned before ECMO initiation 81.…”
Section: Additional Therapiesmentioning
confidence: 99%